Investor Sentiment and Stock Price Crash Risk: Evidence from China. Issue 4 (2nd October 2021) - Fan, Yunqi; Zhou, Fangzhao; An, Yunbi; Yang, Jun
ABSTRACT: We study the cross-sectional effects of investor sentiment on stock price crash risk from the perspective of investor behavioural biases. We develop a firm-specific investor sentiment measure, and find that stocks with stronger investor sentiment are more prone to a future price crash. The positive relation is more pronounced for stocks eligible for margin trading, as higher investor sentiment induces greater margin buy/cover by optimistic investors. Short interest moderates the impact of optimistic sentiment on crash risk. The positive relation is also particularly prominent for stocks with a more speculative appeal, especially for those with lower institutional ownership.